AN APPRAISAL ON CUSTOMER SERVICE OF INDIA POST - Amit Kumar Chakrabarty (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2025)
This paper deals with the customer service of a head post office (HPO) under India Post. Data have been collected personally from 100 account holders of the post office. Account holders have been selected at random basis. A questionnaire has been used to collect the primary data. Data has been analyzed through different tables and using statistical tests. In this study, it was found that most of the account holders are satisfied with how the post office provides customer service.